Penguatan Literasi Digital melalui Gen-AI Writing Assistant–Integrated Digital Writing Platform Menuju Indonesia Emas 2045 pada Siswa SMA Kota Cirebon - Utami Rosalina; Nunik Nur Rahmi Fauzah; Asep Kosasih; Mochamad Guntur; Brahmanto Seno; Rissa Januar (Program Studi Pendidikan Guru Sekolah Dasar Universitas Flores Ende, 2026)
The development of Generative Artificial Intelligence (Gen-AI) provides new opportunities to support learning transformation, especially in learning to write English. However, the use of this technology requires strengthening digital literacy and understanding the ethics of using AI by teachers so that it can be appropriately integrated in the learning process. This community service activity aims to strengthen teachers' digital literacy through the Gen-AI Writing Assistant–Integrated Digital Writing Platform Workshop at SMAN 5 Cirebon City. The activity was carried out using a participatory approach through the stages of preparation, workshop implementation, discussion, and reflection. The material presented included the basic concepts of Gen-AI, digital literacy, the use of Gen-AI Writing Assistant in learning to write English, prompt preparation techniques, and ethics and academic integrity in the use of AI. In addition to delivering the material, the speakers demonstrated the main features of the digital writing platform and opened an interactive discussion session with teachers. The results showed that participants gained a better understanding of the potential and challenges of using Gen-AI in learning, and showed high enthusiasm through discussions on AI integration strategies in the classroom. The workshop also serves as a forum for sharing experiences and building awareness about the importance of using AI critically, ethically, and responsibly. This activity is expected to be the first step in strengthening teachers' digital competence and becoming a model of professional development that can be replicated in other schools to support the transformation of education towards a Golden Indonesia 2045.